Análisis de la licencia social en Colombia y su impacto en la industria petrolera (2024)
The oil industry is a key sector for the Colombian economy, but its development can have a negative impact on affected communities. Therefore, it is important to have the social license of these communities, which refers to their prior, free and informed consent. The general objective of this research is to propose a strategy to improve the perception of the practices, concepts, social and environmental benefits of the extractive projects of the oil industry in the communities surrounding the areas of influence.